Cross-border effects of capacity mechanisms in electricity markets - Christina Elberg (Institute of Energy Economics at the University of Cologne (EWI), 2014)
To ensure security of supply in liberalized electricity markets, different types of capacity mechanisms are currently being debated or have recently been implemented in many European countries. The purpose of this study is to analyze the cross-border effects resulting from different choices on capacity mechanisms in neighboring countries. We consider a model with two connected countries that differ in the regulator's choice on capacity mechanism, namely strategic reserves or capacity payments. In both countries, competitive firms invest in generation capacity before selling electricity on the spot market. We characterize market equilibria and find the following main result: While consumers' costs may be the same under both capacity mechanisms in non-connected countries, we show that the different capacity mechanisms in interconnected countries induce redistribution effects. More precisely, we find that consumers' costs are higher in countries in which reserve capacities are procured than in countries in which capacity payments are used to ensure the targeted reliable level of electricity.
Keywords: D47; Q41; 330; Electricity Markets; Capacity Mechanisms; Cross-Border Effects